Kesatuan dan Perbedaan dalam Gereja Perdana - Victor Christianto (Indonesian Journal of Theology, 2014)
Two interesting questions in relation to the Early Church history are the extent of unity or diversity among Peter, James, and Paul; and also how Paul's thoughts have shaped the direction of the Church in later periods. Answers to these questions will be very helpful in order that we can give a proper response to "Paulinism", an accusation which some non-Christian thinkers often have towards Christians (c.f. Tom Jacobs). Such an accusation (Paulinism) basically says that Christianity is a religion created by St. Paul, not Jesus Christ. In order to respond to such an accusation, in this article the writer will describe: what was the historical truth concerning relation between St. Paul and the Jerusalem Church generally, and especially the relation between St. Paul and James the brother of Jesus. It will be shown that the relationship between St. Paul and the Jerusalem Church did not indicate separation or conflict, but unity in diversity. This article is written with a purpose to open a new constructive way of interfaith dialogue; nonetheless, this is just preliminary research, therefore, this article may not give the last word or a definitive answer to the problems posed above.